2020
DOI: 10.1051/e3sconf/202018401067
|View full text |Cite
|
Sign up to set email alerts
|

A Role of cryogenic in Wire cut EDM process

Abstract: Novel techniques are being focused on the enrichment of the performance characteristics under different machining processes. Cryogenic is one of such novel practices that tunes the surface integrity with vast variations with the traditional machining processes. Dimensional accuracy, surface roughness, material removal rate with less reduction in scrap of material is one of the prior targets of production process. Wire cut Electro Discharge Machining (WEDM) is one method that satisfy with upgrading performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Taguchi analysis of MRR of NDWEDM and cryogenic cooled NDWEDM are shown in tables 6 and 7. In the NDWEDM, the contribution of control variables on MRR was 28.60% pulse width, 22.38% current, 15.70% air pressure, 15.11% pulse interval, and 4.93% The MRR has been increased by increasing pulse width from 15 μs to 25 μs due to more debris due to increase the size of the crater and reduce the spark intensity [27]. It has also been increased by increasing spark current from 3A μs to 5A due to high spark intensity between the wire and workpiece [24].…”
Section: Process Parameters Influence On Mrrmentioning
confidence: 99%
See 1 more Smart Citation
“…Taguchi analysis of MRR of NDWEDM and cryogenic cooled NDWEDM are shown in tables 6 and 7. In the NDWEDM, the contribution of control variables on MRR was 28.60% pulse width, 22.38% current, 15.70% air pressure, 15.11% pulse interval, and 4.93% The MRR has been increased by increasing pulse width from 15 μs to 25 μs due to more debris due to increase the size of the crater and reduce the spark intensity [27]. It has also been increased by increasing spark current from 3A μs to 5A due to high spark intensity between the wire and workpiece [24].…”
Section: Process Parameters Influence On Mrrmentioning
confidence: 99%
“…The high-strength low alloy is cut by cryogenically treated brass wire to compare the cutting speed with the untreated process [26]. In 2020, the influence of various parameters on different work materials using cryogenically cooled wire tools in conventional WEDM processes has been deeply reviewed [27]. Very recently, It was concluded that the wear rate of the molybdenum wire electrode was reduced by cryogenic cooled treatments [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that 13.25% of tool wear and 15.75% in surface irregularity have been reduced by the cryogenically treated EDM process [41,42]. Dimensional accuracy, tool wear rate, surface roughness, the material removal rate of cryogenic treated WEDM process have been investigated to find the best parameters [43]. As per the aforementioned literature, the cryogenic treated tools and workpieces were experimented with reducing the TWR, and SR, and increased the MRR by controlling various parameters in the conventional EDM and WEDM processes.…”
Section: Introductionmentioning
confidence: 99%